The impact of earning management on market earnings value: the causal study on the level of accruals - Muljanto Siladjaja; Yuli Anwar (The Accounting Journal of Binaniaga, 2019)
The purpose of this research is to test investors capability to detect earning management after the period of publication, when the information from financial report plays critical role in investment’s decision. Given the feedback of investor’s reaction, this research provides an empirical model, that point out the earnings management as a message or signal of firm performance, particularly of negative perception on accruals’s opportunisties. This research uses path model analysis and multivariate regression, where the data have been collected from 2.560 observations. The unit of analysis of this research was all the listed companies in the period 20012017. The method of sampling was purposive sampling, which based on annual financial report. The findings of this research showed that all public firms have systematic method for earnings management, by distinguishing the positive and negative accruals, the discretionary accruals have the negative influence on the market value significantly, when we used the earning market ratio. When financial report had high accruals quality, it had positive perception from investors, while estimating the future prospect with high accuracy by obtaining usefulness of financial report. The indicator of earnings management, and working capital had been sensitive for investors, because of accruals in reporting firm’s performance. Keywords: Discretionary Accruals, Working Capital, Dividend Pay Out, Quality of Accruals, Cost of Capital.